REGIMES OF DRIP IRRIGATION, WATER CONSUMPTION AND PRODUCTIVITY OF AN EARLY-RIPENING ONION IN A STEPPE ZONE OF UKRAINE - A. Shatkovsky; V. Vasyuta; A. Zhuravlev; Yu. Cherevychny (Овощи России, 2015)
The results of investigation of of the basic parameters of drip irrigation regimes, total water consumption and productivity of the early-ripening onion in a dry Steppe of Ukraine depending on the soil’s pre-irrigation humidity are presented. It was found that maximal yield was obtained when the pre-irrigation humidity was 90% at the minimal specific consumption of irrigating water for development of 1 ton of products.